Description of Knowledge of Stunting Children about Animal Food, Attitude and Behavior in Feeding at Gunggungan Lor Village, Probolinggo District - Dinda Maulidiyah; Inne Soesanti; Nur Hatijah; Mujayanto (Politeknik Kesehatan Kemenkes Surabaya, 2023)
Severe nutritional deficiencies, including growth retardation, are infant conditions caused by malnutrition that result in being smaller than their age indicates. Factors that influence stunting in young children include direct factors such as diet and infectious diseases, as well as indirect factors such as nutrition, parenting, food transmission, and family knowledge. This research is useful to know of mothers of stunted infants about animal foods and their attitudes and behaviors when providing such foods in the village of Gungungan Roll, Probolinggo Regency. is. The research method used was descriptive. The study involved 38 mothers with stunted children aged 12 to 60 months. Data were collected by questionnaire-based interviews. Studies show that most stunted infants are between 42 and 58 months of age. The results also indicate a lack of animal protein due to low consumption of animal food. Most mothers have good knowledge (23 or 60.5%), agreeable attitudes (33 or 86.8%), but exhibit inadequate behavior (22 or 57.9%) in providing animal-based dishes. Mothers of stunted toddlers with good knowledge are more receptive and respond well to explanations about the condition, influencing their attitudes towards it.